Windows 10 For Seniors For Dummies, 4th Edition - Weverka, Peter (For Dummies, 2020)
The easy way to get up and running with Windows 10! With Windows 10 For Seniors For Dummies , becoming familiarized with Windows 10 is a painless process. If you're interested in learning the basics of this operating system without having to dig through confusing computer jargon, look no further. This book offers a step-by-step approach that is specifically designed to assist first time Windows 10 users who are over-50, providing easy-to-understand language, large-print text, and an abundance of helpful images along the way! Protect your computer Follow friends and family online Use Windows 10 to play games and enjoy media Check your security and maintenance status Step-by-step instructions are provided to ensure that you don't get lost at any point along the way.
Online resource; Title from title page (viewed August 25, 2020)
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Computers and older people; Systèmes d'exploitation (Ordinateurs); Ordinateurs et personnes âgées; operating systems